Discontinuities in quinoa biodiversity in the dry Andes: An 18 - century perspective based on allelic genotyping - Winkel, Thierry; Aguirre, María Gabriela; Arizio, Carla Marcela; Aschero, Carlos A.; Babot, María del Pilar; Benoit, Laure; Burgarella, Concentta; Costa Tártara, Sabrina María; Dubois, Marie - Pierre; Gay, Laurene; Hocsman, Salomon; Margaux, Jullien; et al. (Plos ONE, 2021)
History and environment shape crop biodiversity, particularly in areas with vulnerable human communities and ecosystems. Tracing crop biodiversity over time helps understand how rural societies cope with anthropogenic or climatic changes. Exceptionally well preserved ancient DNA of quinoa (Chenopodium quinoa Willd.) from the cold and arid Andes of Argentina has allowed us to track changes and continuities in quinoa diversity over 18 centuries, by coupling genotyping of 157 ancient and modern seeds by 24 SSR markers with cluster and coalescence analyses. Cluster analyses revealed clear population patterns separating modern and ancient quinoas. Coalescence-based analyses revealed that genetic drift within a single population cannot explain genetic differentiation among ancient and modern quinoas. The hypothesis of a genetic bottleneck related to the Spanish Conquest also does not seem to apply at a local scale. Instead, the most likely scenario is the replacement of preexisting quinoa gene pools with new ones of lower genetic diversity. This process occurred at least twice in the last 18 centuries: first, between the 6th and 12th centuries-a time of agricultural intensification well before the Inka and Spanish conquests-and then between the 13th century and today-a period marked by farming marginalization in the late 19th century likely due to a severe multidecadal drought. While these processes of local gene pool replacement do not imply losses of genetic diversity at the metapopulation scale, they support the view that gene pool replacement linked to social and environmental changes can result from opposite agricultural trajectories.